2019
DOI: 10.1002/htj.21598
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of non‐Newtonian magnetohemodynamic flow conveying nanoparticles through a stenosed coronary artery

Abstract: The present study considers two-dimensional mathematical modeling of non-Newtonian nanofluid hemodynamics with heat and mass transfer in a stenosed coronary artery in the presence of a radial magnetic field. The second-grade differential viscoelastic constitutive model is adopted for blood to mimic non-Newtonian characteristics, and blood is considered to contain a homogenous suspension of nanoparticles. The Vogel model is employed to simulate the variation of blood viscosity as a function of temperature.The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…These phenomena can also be exploited in medical engineering applications which include cardiovascular flow control [28], MHD based biomedical micro‐pumps, micro‐bio‐mixers, blood cell manipulation (owing to haemoglobin content) [29], magnetohydrodynamic (MHD) microfluidic platforms for cell switching [30], magneto‐robotic endoscopy [31], electrocardiogram interaction with MHD [32], cardiac cycle synchronization of magnetic resonance imaging (MRI). Recent studies in computational simulations of magnetohydrodynamic medical flows have also examined a wide spectrum of applications including magneto‐micro‐robotic propulsion for embryological treatment [34], biomagnetic therapy [35], gastric endoscopy [36], bio‐inspired nanofluid smart micro‐pumps [37] and radiation tissue electromagnetic treatments [38]. These studies have confirmed that magnetic effects offer significant benefits in biomedical systems and have the advantage of being non‐intrusive and relatively easy to implement [39].…”
Section: Introductionmentioning
confidence: 99%
“…These phenomena can also be exploited in medical engineering applications which include cardiovascular flow control [28], MHD based biomedical micro‐pumps, micro‐bio‐mixers, blood cell manipulation (owing to haemoglobin content) [29], magnetohydrodynamic (MHD) microfluidic platforms for cell switching [30], magneto‐robotic endoscopy [31], electrocardiogram interaction with MHD [32], cardiac cycle synchronization of magnetic resonance imaging (MRI). Recent studies in computational simulations of magnetohydrodynamic medical flows have also examined a wide spectrum of applications including magneto‐micro‐robotic propulsion for embryological treatment [34], biomagnetic therapy [35], gastric endoscopy [36], bio‐inspired nanofluid smart micro‐pumps [37] and radiation tissue electromagnetic treatments [38]. These studies have confirmed that magnetic effects offer significant benefits in biomedical systems and have the advantage of being non‐intrusive and relatively easy to implement [39].…”
Section: Introductionmentioning
confidence: 99%
“…To maintain cell-level metabolism, blood flow ensures the transportation of nutrients, hormones, metabolic wastes, 2 O , and 2 CO throughout the body. It regulates the pH, osmotic pressure and temperature of the whole body and protects the body from microbial and mechanical harm [7]. A significant number of studies have been reported by considering blood as a Newtonian fluid.…”
Section: Introductionmentioning
confidence: 99%